2019
DOI: 10.1002/ajim.23019
|View full text |Cite
|
Sign up to set email alerts
|

Associations between daily‐on‐the job hassles with perceived mental exertion and depression symptoms in taxi drivers

Abstract: Introduction Taxi drivers experience frequent hassles that may contribute to mental exertion and depression symptoms. Aim Mental exertion and depression symptoms in taxi drivers are explored in association with hassles, effort‐reward imbalance, job strain, and iso‐strain. Methods Personal interviews were conducted with 130 drivers in San Francisco. Results Mental exertion averaged 4.5 (±2.68) and physical exertion averaged 3.71 (±2.1) on 0 to 10 Borg scales. Based on the Center for Epidemiological Studies‐Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
2
2
0
Order By: Relevance
“…The online survey and input from the PAG further support previously reported associations between taxi driving and higher perceived levels of psychological stress [ 4 , 6 , 9 , 51 , 52 , 56 , 57 , 58 ]. Increased stress is caused by financial pressures, long working hours, and abusive customers.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The online survey and input from the PAG further support previously reported associations between taxi driving and higher perceived levels of psychological stress [ 4 , 6 , 9 , 51 , 52 , 56 , 57 , 58 ]. Increased stress is caused by financial pressures, long working hours, and abusive customers.…”
Section: Discussionsupporting
confidence: 79%
“…The online survey and conversations held with taxi drivers during PAG meetings helped uncover knowledge regarding the working lives of taxi drivers in Northern Ireland, data previously unexplored. Similar to previous research conducted with taxi drivers in other countries [ 5 , 9 , 13 , 14 , 56 , 57 ], those working in Northern Ireland had been in the job for an average of 11 years. Of concern is the significant association reported between working as a taxi driver for more than ten years and an increased risk of both CVD [ 9 ] and myocardial infarction [ 12 ].…”
Section: Discussionsupporting
confidence: 72%
“…Seven quantitative studies reported workers' rights (21,23,40,59,64,69) with three of them yielding evidence for an association between lack workers' rights and mental health outcomes (21,59,64).…”
Section: Precarious Employment and Its Association With Mental Healthmentioning
confidence: 99%
“…Scand J Work Environ Health -online first Precarious employment and mental health in migrant workers ciation between precarious employment and physical health problems such as musculoskeletal issues (17), cardiovascular diseases (18), occupational accidents and injury (19,20). Results of other studies also show that precarious work conditions have an influence on mental health problems such as depression (21), anxiety and stress (22), suicidal ideation (23,24), sleep issues and burnout (24)(25)(26). Accordingly, there are a number of systematic reviews that have synthesized the evidence for detrimental mental health effects of different dimensions of precarious employment (5,9,(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%